Preparation method and application of in-situ electrodeposited zinc negative electrode protective film based on covalent triazine framework

By using the in-situ electrodeposition technology of covalent triazine frame in zinc ion batteries, the problems of zinc dendrites growth and hydrogen evolution reaction are solved, and the stability of zinc negative electrode and the cycle life of the battery are significantly improved.

CN119275223BActive Publication Date: 2025-02-28ANHUI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411795634.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

In zinc-ion batteries, the zinc metal negative electrode is prone to form dendrite and hydrogen evolution reactions during charging and discharge, resulting in low battery safety, poor cycle stability and energy storage efficiency.

Method used

Using the in-situ electrodeposition technology of covalent triazine frame, a dense and uniform protective film is constructed on the surface of the zinc negative electrode, and a covalent triazine frame (CTF-BTH) protective layer is formed through electrical polymerization to inhibit the growth of zinc dendrites and reduce the occurrence of side reactions.

Benefits of technology

It significantly improves the electrochemical stability and reversibility of zinc negative electrode, extends the cycle life of the battery, and enhances the safety and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention discloses a zinc negative electrode protective film based on a covalent triazine framework and an in-situ electrodeposition preparation method and application thereof, and relates to the field of electrochemical energy storage technology. An organic monomer with zinc affinity is in-situ electrodeposited on the surface of a zinc metal negative electrode to form a dense and uniform CTF protective film. The protective film can effectively inhibit the growth of zinc dendrites, reduce side reactions (such as hydrogen evolution reaction), and improve the electrochemical stability and cycle life of the zinc negative electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrochemical energy storage, in particular to a preparation method of an in-situ electrodeposited zinc negative electrode protective film of a covalent triazine framework and application thereof. Background Art

[0002] With the rapid growth of global demand for clean energy and large-scale energy storage, zinc-ion batteries have gradually become a highly anticipated electrochemical energy storage technology due to their abundant zinc resources, low cost, high safety, and environmentally friendly characteristics of aqueous electrolytes. Compared with lithium-ion batteries, the biggest advantage of zinc-ion batteries is that they use aqueous electrolytes, which can significantly reduce the safety risks of batteries and have higher ion mobility. However, zinc metal anodes face a series of severe technical challenges in practical applications, which seriously limit their practical applications in long-cycle stability and efficient energy storage.

[0003] 1. Zinc dendrite growth: During the charge and discharge process, the non-uniform deposition of zinc ions on the negative electrode surface is prone to lead to the growth of zinc dendrites. The formation of zinc dendrites will not only pierce the separator, causing battery short circuit, greatly reducing the safety of the battery, but also cause irreversible loss of active zinc materials in the negative electrode, resulting in a significant decrease in coulombic efficiency and cycle stability.

[0004] 2. Side reaction problem: Due to the narrow electrochemical window of aqueous electrolytes, the zinc negative electrode is prone to hydrogen evolution reaction (HER) during charging. The occurrence of this side reaction will cause H + It is reduced to hydrogen on the zinc surface, which consumes the zinc material and further aggravates the electrode surface passivation and structural damage. This not only reduces the energy efficiency of the battery, but also leads to severe electrode corrosion.

[0005] 3. Uneven deposition on the electrode surface: Uneven deposition of zinc ions on the electrode surface will lead to excessive local current density, which will in turn aggravate dendrite growth and side reactions. In addition, due to the strong activity of zinc metal, it is very easy to react with the electrolyte to generate unstable byproducts, which further weakens the electrochemical performance of the negative electrode.

[0006] In order to solve the above problems, researchers have proposed a variety of zinc negative electrode protection strategies in recent years, including the use of functionalized electrolyte additives, coating of high-stability protective films, and design of three-dimensional structured electrodes. However, these strategies still have shortcomings in practical applications. For example, the coated protective film is easy to fall off or decompose during the electrochemical process, and it is difficult to maintain the protective effect on the zinc negative electrode for a long time; and although the three-dimensional structure electrode can alleviate the local current density concentration, its manufacturing process is complicated and the cost is high. Therefore, there is an urgent need for a simple, effective and industrially applicable zinc negative electrode protection technology. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the purpose of the present invention is to provide a method for preparing an in-situ electrodeposited zinc negative electrode protective film of a covalent triazine framework and its application. The present invention aims to effectively inhibit the growth of zinc dendrites and reduce the occurrence of side reactions (such as hydrogen evolution reaction), thereby significantly improving the electrochemical stability and reversibility of the zinc negative electrode.

[0008] To achieve the above object, the technical solution adopted by the present invention is: a method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework, comprising the following steps:

[0009] Step 1, dissolving a 2,4,6-tri(2-thienyl)-1,3,5-triazine precursor in a mixed solution of acetonitrile and dichloromethane, adding tetrabutylammonium perchlorate, performing ultrasonic dispersion treatment at room temperature, and continuously stirring to obtain a uniform precursor solution;

[0010] Step 2, immersing the zinc metal negative electrode in the obtained precursor solution, and then performing an electropolymerization reaction in a three-electrode system; under a constant voltage condition, performing an electrodeposition reaction for different times to construct a covalent triazine framework protective layer;

[0011] Step 3: After the electrodeposition is completed, the obtained CTF-BTH@Zn electrode having a covalent triazine framework protective layer on the surface is taken out from the solution and rinsed and dried to ensure that the protective film is fully cured.

[0012] As a further improvement of the present invention, in step 1, the volume ratio of acetonitrile to dichloromethane is 3:1.

[0013] As a further improvement of the present invention, in step 1, the volume of the precursor solution is 20-25 mL, the mass of the precursor substance is 5.26-11.11 mg, and the concentration of tetrabutylammonium perchlorate is 0.1 M.

[0014] As a further improvement of the present invention, in step 1, the ultrasonic dispersion treatment time is 50-60 minutes, and the stirring time is 20-30 minutes.

[0015] As a further improvement of the present invention, in step 2, the electropolymerization reaction is carried out using the Ag / AgCl electrode as the reference electrode, the platinum sheet as the counter electrode, and the zinc metal negative electrode as the working electrode.

[0016] As a further improvement of the present invention, in step 2, the mass of the zinc metal negative electrode is 90-100 mg, the voltage range of the electrodeposition reaction is 1.0 V-1.5 V, and the electrodeposition time range is 5-60 minutes.

[0017] As a further improvement of the present invention, in step 3, the vacuum drying temperature is 60-100° C., and the drying time is 8-16 hours.

[0018] The present invention also provides a CTF-BTH@Zn electrode based on a covalent triazine framework prepared by the preparation method as described above.

[0019] The present invention also provides a use of the CTF-BTH@Zn electrode as described above in an aqueous zinc ion battery.

[0020] As a further improvement of the present invention, the CTF-BTH@Zn electrode is used as an electrode of an aqueous zinc ion battery to assemble an aqueous zinc ion battery.

[0021] The present invention forms a dense and uniform protective film on the surface of the zinc negative electrode by in-situ polymerization, so as to significantly improve the electrochemical performance and long-cycle stability of the zinc negative electrode. CTF material is an organic porous framework structure with high chemical stability and excellent conductivity. Through in-situ electrodeposition technology, it can be uniformly deposited on the surface of the zinc negative electrode, thereby effectively inhibiting the growth of zinc dendrites. The rich C=N functional groups promote the uniform deposition of zinc ions and reduce the occurrence of side reactions such as hydrogen evolution reaction (HER).

[0022] The CTF-BTH@Zn electrode prepared by the present invention has a dense and uniform covalent triazine framework protective layer, can effectively inhibit the growth of zinc dendrites, and significantly improve the long-cycle stability of zinc ion batteries, and is suitable for negative electrode materials of aqueous zinc ion batteries.

[0023] The mechanism of the present invention is as follows:

[0024] The present invention solves the problem that zinc negative electrode is easy to form dendrites and side reactions in aqueous zinc ion batteries by constructing a covalent triazine framework (CTF-BTH) protective layer on the surface of zinc metal negative electrode. When zinc metal works in aqueous electrolyte, zinc ions (Zn 2+ ) on the negative electrode surface, which can easily cause the growth of zinc dendrites, which can pierce the battery separator and cause the battery to short-circuit. At the same time, zinc metal is prone to hydrogen evolution reaction (HER) during the electrochemical reaction, further accelerating the corrosion and failure of zinc metal. By depositing a dense and uniform covalent triazine framework protective layer on the surface of zinc metal, the covalent triazine framework (CTF-BTH) as an ordered porous organic structure has abundant active sites, which can uniformly adsorb zinc ions (Zn 2+ ), promoting its uniform distribution on the negative electrode surface. The nitrogen and sulfur elements in the covalent triazine framework have good affinity with zinc, and the formation of chemical bonds further enhances the uniformity of zinc ion deposition on the negative electrode surface, thereby avoiding the problem of dendrite growth caused by excessive local current density, promoting the desolvation process of zinc ions, and accelerating the deposition and stripping process of zinc ions.

[0025] From the perspective of practical application, the present invention designs a method for constructing a covalent triazine framework protective layer for in-situ electrodeposition of zinc negative electrode suitable for aqueous zinc ion battery system. Through this process, a uniform covalent triazine framework protective film is constructed by in-situ electrodeposition on the surface of the zinc negative electrode. The protective film is directly generated by an electrochemical deposition process, which has a simple process, low cost, and is suitable for large-scale application. The covalent triazine framework has good zinc affinity, can effectively promote the uniform deposition of zinc ions, and prolong the cycle life of the battery by reducing side reactions. In addition, the close combination between the protective film and the zinc metal enables it to maintain a high electrochemical stability at high current density, avoid the growth of zinc dendrites, and significantly improve the safety and performance of zinc-based batteries.

[0026] The beneficial effects of the present invention are:

[0027] 1. By constructing a covalent triazine framework (CTF-BTH) protective film on the surface of the zinc metal negative electrode, the present invention significantly inhibits the growth of zinc dendrites. The covalent triazine framework has good zinc affinity and can uniformly adsorb Zn 2+ It guides the uniform deposition of zinc on the negative electrode surface to prevent the problem of zinc dendrite growth caused by excessive local current density. This effectively improves the safety of the zinc negative electrode and reduces the risk of short circuit caused by zinc dendrites piercing the diaphragm.

[0028] 2. The CTF-BTH protective film formed by the present invention through the optimized electrodeposition process has good chemical stability and mechanical strength, and can significantly improve the electrochemical performance of the zinc negative electrode. The film layer not only inhibits the occurrence of side reactions (such as hydrogen evolution reaction, HER), but also reduces the electrode polarization effect and improves the cycle stability of the electrode. In the long-term cycle test, the negative electrode showed excellent stability and the cycle life of the battery was significantly extended.

[0029] 3. The in-situ electrodeposition technology used in the present invention is simple and easy to control, and is suitable for large-scale production. By optimizing the polymerization time, voltage and solution concentration, the film thickness and structure can be accurately controlled, thereby achieving uniformity and performance optimization of the protective film. The entire preparation process does not require complex post-processing steps, has strong operability and repeatability, and is suitable for industrial applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM images of the CTF-BTH@Zn electrodes with different polymerization times prepared in Example 1 of the present invention show the surface morphology of the covalent triazine framework protective film constructed on the surface of the zinc negative electrode.

[0031] Figure 2 This is the infrared spectrum of the CTF-BTH@Zn electrode prepared in Example 1 of the present invention, characterizing the chemical bond characteristics of the covalent triazine framework.

[0032] Figure 3 The XRD patterns of the CTF-BTH@Zn electrode and the bare zinc electrode prepared in Example 1 of the present invention after long-term immersion in zinc sulfate electrolyte demonstrate the corrosion resistance of the CTF-BTH protective film on the zinc negative electrode.

[0033] Figure 4 The symmetrical battery assembled by the membrane-protected three-dimensional porous zinc electrode and the symmetrical battery assembled by the bare zinc electrode in Example 1 of the present invention were tested at 5 mA·cm -2 The current density and 1 mAh cm -2 Voltage-time curve of cycling at surface capacity.

[0034] Figure 5 yes Figure 4 Schematic diagram of the number of circles in the middle part.

[0035] Figure 6 This is the Tafel slope curve of the membrane-protected CTF-BTH@Zn electrode and the bare zinc electrode in sodium sulfate buffer solution in Example 1 of the present invention.

[0036] Figure 7 This is a comparison diagram of the zinc dendrite inhibition effect of the CTF-BTH@Zn electrode prepared in Example 1 of the present invention and the bare zinc electrode, wherein A is the CTF-BTH@Zn electrode, and B is the bare zinc electrode. The scanning electron microscope (SEM) image shows the surface morphology after a long cycle test, indicating the excellent performance of the CTF-BTH protective film in inhibiting zinc dendrites.

[0037] Figure 8 This is a comparison diagram of the hydrogen evolution overpotential of the CTF-BTH@Zn electrode and the bare zinc electrode measured by linear sweep voltammetry (LSV) in Example 1 of the present invention. The figure shows the significant effect of the CTF-BTH protective film in inhibiting the hydrogen evolution reaction, indicating that the CTF-BTH@Zn electrode modified with the protective film has a higher hydrogen evolution overpotential, significantly reducing the tendency of side reactions in the aqueous electrolyte, thereby improving the electrochemical stability of the electrode. DETAILED DESCRIPTION

[0038] The embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0039] Example 1

[0040] In this example, the CTF-BTH@Zn electrode was prepared according to the following steps:

[0041] Step 1: 9.8 mg of 2,4,6-tri(2-thienyl)-1,3,5-triazine precursor was dissolved in a mixed solution of 24 ml of acetonitrile and dichloromethane, followed by the addition of 0.1 M tetrabutylammonium perchlorate. The mixed solution was ultrasonically dispersed at room temperature and stirred for 50 minutes to ensure that the precursor was fully dissolved to obtain a uniform precursor solution, wherein the volume of the precursor solution was 24 mL and the mass of the precursor was 9.8 mg.

[0042] Step 2: Immerse the zinc metal negative electrode in the precursor solution obtained in step 1, and perform an electropolymerization reaction in a three-electrode system. With Ag / AgCl as the reference electrode, platinum sheet as the counter electrode, and zinc metal negative electrode as the working electrode, electrodeposition is performed at a constant voltage of 1.2 V, and the electrodeposition time can be adjusted according to specific requirements to form a covalent triazine framework protective layer.

[0043] Step 3: After the electrodeposition is completed, the CTF-BTH@Zn electrode is taken out of the solution and the electrode surface is rinsed with acetonitrile and ethanol 4 times respectively to remove the impurities remaining during the deposition process. After cleaning, the electrode is placed in a vacuum drying oven at 80°C and dried for 12 hours.

[0044] Figure 1 The SEM images of the CTF-BTH@Zn electrodes with different polymerization times prepared in Example 1 of the present invention show the surface morphology of the covalent triazine framework protective film constructed on the surface of the zinc negative electrode. As the polymerization time changes, the thickness and uniformity of the film layer show significant changes. The SEM image clearly shows that the protective film at 15 minutes has the best uniformity and density, indicating that the electrodeposition conditions at this time point are most suitable for forming a stable protective film.

[0045] Figure 2 The infrared spectrum of the CTF-BTH@Zn electrode prepared in Example 1 of the present invention characterizes the chemical bond characteristics of the covalent triazine framework. Infrared spectroscopy (FTIR) analysis shows that there are typical C=N and CS bond peaks in the CTF-BTH protective film, verifying the successful formation of the covalent triazine framework structure. The stability of this chemical structure provides a guarantee for the long-term electrochemical performance of the electrode.

[0046] Figure 3 The XRD patterns of the CTF-BTH@Zn electrode and the bare zinc electrode prepared in Example 1 of the present invention after long-term immersion in zinc sulfate electrolyte show the corrosion resistance of the CTF-BTH protective film on the zinc negative electrode. Compared with the bare zinc electrode, the CTF-BTH@Zn electrode has no obvious signs of corrosion on the surface after immersion, indicating that the protective film effectively isolates the direct corrosion of the electrolyte on the zinc negative electrode and improves the corrosion resistance of the electrode.

[0047] Figure 4The symmetrical battery assembled with the membrane-protected three-dimensional porous zinc electrode and the symmetrical battery assembled with the bare zinc electrode in Example 1 was 5 mA·cm -2 The current density and 1 mAh·cm -2 The voltage-time curve of the CTF-BTH@Zn electrode shows a lower voltage polarization and a more stable voltage platform, indicating that the protective film significantly improves the cycling stability and electrochemical performance of the zinc negative electrode.

[0048] Figure 5 yes Figure 4 Schematic diagram of the number of circles in the middle. In the figure, the CTF-BTH@Zn electrode shows a low polarization voltage, with small and stable voltage fluctuations, indicating that the zinc deposition / dissolution process is uniform and the electrode stability is high. However, at the bare zinc level, the polarization voltage fluctuates greatly, showing unstable deposition / dissolution behavior, which may be affected by zinc dendrite growth and side reactions.

[0049] Figure 6 The Tafel slope curves of the membrane-protected CTF-BTH@Zn electrode and the bare zinc electrode in sodium sulfate buffer solution in Example 1. The CTF-BTH@Zn electrode shows a larger Tafel slope, indicating that the corrosion current density of the electrode is low and has excellent corrosion resistance. The Tafel slope shows that the CTF-BTH film layer has a significant protective effect on the zinc negative electrode.

[0050] Figure 7 This is a comparison diagram of the zinc dendrite inhibition effect of the CTF-BTH@Zn electrode prepared in Example 1 of the present invention and the bare zinc electrode. The scanning electron microscope (SEM) image shows the surface morphology after a long cycle test, indicating the excellent performance of the CTF-BTH protective film in inhibiting zinc dendrites. Figure 7 The surface of the CTF-BTH@Zn electrode in A remains flat after long-term cycling, while Figure 7 Dendrites appeared on the surface of the bare zinc electrode in B, proving that the CTF-BTH protective film effectively inhibited the growth of zinc dendrites.

[0051] Figure 8 The figure is a comparison of the hydrogen evolution overpotentials of the CTF-BTH@Zn electrode and the bare zinc electrode measured by linear sweep voltammetry (LSV) in Example 1. The CTF-BTH@Zn electrode shows a higher hydrogen evolution overpotential, indicating that it has a significant inhibitory effect on the hydrogen evolution reaction in an aqueous electrolyte, further verifying the excellent performance of the protective film in reducing the tendency of side reactions and improving the electrochemical stability of the electrode.

[0052] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework, characterized in that: The following steps are involved: Step 1, dissolving a 2,4,6-tri(2-thienyl)-1,3,5-triazine precursor in a mixed solution of acetonitrile and dichloromethane, adding tetrabutylammonium perchlorate, performing ultrasonic dispersion treatment at room temperature, and continuously stirring to obtain a uniform precursor solution; Step 2, immersing the zinc metal negative electrode in the obtained precursor solution, and then performing an electropolymerization reaction in a three-electrode system; under a constant voltage condition, performing an electrodeposition reaction for different times to construct a covalent triazine framework protective layer; In step 2, the mass of the zinc metal negative electrode is 90-100 mg, the voltage range of the electrodeposition reaction is 1.0 V-1.5 V, and the electrodeposition time range is 15-30 minutes; Step 3: After the electrodeposition is completed, the zinc electrode having the covalent triazine framework protective layer on the surface is taken out from the solution and rinsed and dried to ensure that the protective film is fully cured.

2. The method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework according to claim 1, characterized in that: In step 1, the volume ratio of acetonitrile to dichloromethane is 3:

1.

3. The method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework according to claim 1, characterized in that: In step 1, the volume of the precursor solution is 20-25 mL, the mass of the precursor substance is 5.26-11.11 mg, and the concentration of tetrabutylammonium perchlorate is 0.1 M.

4. The method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework according to claim 1, characterized in that: In step 1, the ultrasonic dispersion treatment time is 50-60 minutes, and the stirring time is 20-30 minutes.

5. The method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework according to claim 1, characterized in that: In step 2, an electropolymerization reaction is carried out using an Ag / AgCl electrode as a reference electrode, a platinum sheet as a counter electrode, and a zinc metal negative electrode as a working electrode.

6. The method for preparing an in-situ electrodeposited zinc negative electrode protective film based on a covalent triazine framework according to claim 1, characterized in that: In step 3, the vacuum drying temperature is 60-100° C., and the drying time is 8-16 hours.

7. A zinc electrode having a covalent triazine framework protective layer on its surface, prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the zinc electrode having a covalent triazine framework protective layer on its surface as claimed in claim 7 in an aqueous zinc ion battery.

9. The use according to claim 8, characterized in that: The zinc electrode with a covalent triazine framework protective layer on its surface is used as an electrode of an aqueous zinc ion battery to assemble an aqueous zinc ion battery.

Citation Information

Patent Citations

  • Preparation and application of poly (2, 4, 6-tri (thiophene-2-yl)-1, 3, 5-triazine) with porous structure

    CN115417978A

  • Preparation method of modified zinc negative electrode and application of modified zinc negative electrode in aqueous zinc ion battery

    CN116759522A